2018
DOI: 10.17113/ftb.56.03.18.5285
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Role of the Whey Culture Medium in the Spray-Drying Microencapsulation of Lactic Acid Bacteria

Abstract: SUMMARYThis study aims to evaluate the multifunctional role of whey culture medium during the spray drying microencapsulation of Lactobacillus fermentum K73. Whey culture medium containing growing microorganisms served to hydrate different mixtures (gum arabic, maltodextrin and whey). We evaluated the use of these mixtures as carbon sources and their protective effects on simulated gastrointestinal conditions. The optimal mixture was spray-dried while varying the outlet temperature and atomizing pressure using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Further downstream processing was performed to simulate a complete manufacturing cycle. Biomass concentration on hollow fibers was the most critical point of the downstream process [4] . Clogging of the membrane, either due to production of EPS, or to the lumen of the hollow fibers, allowed processing of about 11 L of broth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further downstream processing was performed to simulate a complete manufacturing cycle. Biomass concentration on hollow fibers was the most critical point of the downstream process [4] . Clogging of the membrane, either due to production of EPS, or to the lumen of the hollow fibers, allowed processing of about 11 L of broth.…”
Section: Discussionmentioning
confidence: 99%
“…However, very few scientific publications are available on the development of fermentation processes for the large-scale production [ 2 , 19 ]. L. fermentum was demonstrated to grow on renewable feedstocks such as starch [11] , whey [4] , cereal-based substrates [13] and even anaerobic digester sludge [32] . Nevertheless, most studies and patents still use De Man, Rogosa and Sharpe (MRS) medium for bioreactor experiments [ 28 , 33 , 52 ] even if this medium is not well suited for commercial food or pharmaceutical production processes due to presence of animal derived components (beef extract and peptone).…”
Section: Introductionmentioning
confidence: 99%
“…The carrier material was fixed according to the reported by Aragon-Rojas et al . 55 , where an optimization of the carrier material content was developed. The mixture was homogenized with magnetic stirrer during 30 minutes at 130 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…The spray drying method of whey culture medium with 10 6 CFU/g L. plantarum was applied. The whey culture medium is often used as a carrier material for probiotic microencapsulation and generally contains lactose and soluble proteins [ 179 ]. However, a subsequent study found that enrichment of rotifers with two LAB strains between 10 7 and 2 × 10 7 CFU/mL once a day was enough to protect the consuming fish larvae from Vibrio sp.…”
Section: Enrichment With Probioticsmentioning
confidence: 99%